CHARACTERIZATION OF THE BRAZPD II COHORT AND DESCRIPTION OF TRENDS IN PERITONEAL DIALYSIS OUTCOME ACROSS TIME PERIODS - Moraes, Thyago Proenca de; Figueiredo, Ana Elizabeth; Campos, Ludimila Guedim de; Olandoski, Marcia; Barretti, Pasqual [UNESP]; Pecoits-Filho, Roberto (Multimed Inc, 2014)
Observational studies from different regions of the world provide valuable information in patient selection, clinical practice, and their relationship to patient and technique outcome. The present study is the first large cohort providing patient characteristics, clinical practice, patterns and their relationship to outcomes in Latin America. The objective of the present study was to characterize the cohort and to describe the main determinants of patient and technique survival, including trends over time of peritoneal dialysis (PD) initiation and treatment.This was a nationwide cohort study in which all incident adult patients on PD from 122 centers were studied. Patient demographics, socioeconomic and laboratory values were followed from December 2004 to January 2011 and, for comparison purposes, divided into 3 groups according to the year of starting PD: 2005/06, 2007/08 and 2009/10. Patient survival and technique failure (TF) were analyzed using the competing risk model of Fine and Gray. All patients active at the end of follow-up were treated as censored. In contrast, all patients who dropped the study for any reason different from the primary event of interest were treated as competing risk. Significance was set to a p level of 0.05.A total of 9,905 patients comprised the adult database, 7,007 were incident and 5,707 remained at least 90 days in PD. The main cause of dropout was death (54%) and of TF was peritonitis (63%). Technique survival at 1, 2, 3, 4, and 5 years was 91%, 84%, 77%, 68%, and 58%, respectively. There was no change in TF during the study period but 3 independent risk factors were identified: lower center experience, lower age, and automated PD (APD) as initial therapy. Cardiovascular disease (36%) was the main cause of death and the overall patient survival was 85%, 74%, 64%, 54%, and 48% at 1, 2, 3, 4, and 5 years, respectively. Patient survival improved along all study periods: compared to 2005/2006, patients starting at 2007/2008 had a relative risk reduction (SHR) of 0.83 (95% confidence interval [CI] 0.72-0.95); and starting in 2009/2010 of 0.69 (95% CI 0.57-0.83). The independent risk factors for mortality were diabetes, age > 65 years, previous hemodialysis, starting PD modality, white race, low body mass index (BMI), low educational level, center experience, length of pre-dialysis care, and the year of starting PD.We observed an improvement in patient survival along the years. This finding was sustained even after correction for several confounders and using a competing risk approach. On the other hand, no changes in technique survival were found.
Keywords: Peritoneal dialysis; trends; complications; outcome; mortality